2012
DOI: 10.1155/2012/534705
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole-Triggered GSH Synthesis via Activation of Glutamate Transporters to Antagonize Methylmercury-Induced Oxidative Stress in Rat Cerebral Cortex

Abstract: Objective. This study was to evaluate the effect of riluzole on methylmercury- (MeHg-) induced oxidative stress, through promotion of glutathione (GSH) synthesis by activating of glutamate transporters (GluTs) in rat cerebral cortex. Methods. Eighty rats were randomly assigned to four groups, control group, riluzole alone group, MeHg alone group, and riluzole + MeHg group. The neurotoxicity of MeHg was observed by measuring mercury (Hg) absorption, pathological changes, and cell apoptosis of cortex. Oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…The mechanism of action of Riluzole is not very clear, but some studies point to its antioxidant activity by induction of glutathione synthesis, which can only extend survival by 3 months. Edaravone acts as a free radical scavenger [207]. Overwhelming evidence suggests that mitochondrial dysfunction plays a significant role in proteinopathies of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action of Riluzole is not very clear, but some studies point to its antioxidant activity by induction of glutathione synthesis, which can only extend survival by 3 months. Edaravone acts as a free radical scavenger [207]. Overwhelming evidence suggests that mitochondrial dysfunction plays a significant role in proteinopathies of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The present data indicated that glutamate alleviated diquat-induced oxidative stress via enhancing SOD, T-AOC, and NO levels and inhibiting lipid oxidation subsequent with MDA generation. It is widely recognized that glutamate exhibits an antioxidant function as glutamate is a precursor for glutathione (GSH) along with cysteine and glycine [ 33 ]. In our lab, we have found that glutamate is the main limiting substrate compared with cysteine and glycine for liver GSH synthesis in mice (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Excitotoxic levels of glutamate induce oxidative stress (Trotti et al, 1998), and this negative self‐regulation could be a relevant mechanism in neurodegenerative diseases. Riluzole has already been shown to exert a beneficial effect on oxidative stress when induced by diverse insults, including streptozotocin, sodium nitrite (Rinwa et al, 2012) and methylmercury (Deng et al, 2012). Here, we show that riluzole had an antioxidant effect and diminished the total reactive oxygen species load.…”
Section: Discussionmentioning
confidence: 99%